2001
DOI: 10.1104/pp.125.2.955
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Molecular-Physiological Study of Submergence Response in Lowland and Deepwater Rice

Abstract: Survival of rice (Oryza sativa) upon an extreme rise of the water level depends on rapid stem elongation, which is mediated by ethylene. A genomic clone (OS-ACS5) encoding 1-aminocyclopropane-1-carboxylic acid (ACC) synthase, which catalyzes a regulatory step in ethylene biosynthesis, has been isolated from cv IR36, a lowland rice variety. Expression was induced upon short-and long-term submergence in cv IR36 and in cv Plai Ngam, a Thai deepwater rice variety. Under hypoxic conditions, abscisic acid and gibber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 52 publications
3
80
1
Order By: Relevance
“…2). Consistent with our results, submergence reduced the endogenous ABA content to a similar extent within 1 day in seedlings of both deepwater and submergence-intolerant lowland rice (20). This shows that the tolerance of prolonged inundation provided by Sub1A is mediated downstream of ABA catabolism and upstream of GA responses.…”
Section: Discussionsupporting
confidence: 79%
“…2). Consistent with our results, submergence reduced the endogenous ABA content to a similar extent within 1 day in seedlings of both deepwater and submergence-intolerant lowland rice (20). This shows that the tolerance of prolonged inundation provided by Sub1A is mediated downstream of ABA catabolism and upstream of GA responses.…”
Section: Discussionsupporting
confidence: 79%
“…GA 1 is the major bioactive GA in rice (Kobayashi et al, 1989). A similar increase in GA levels was shown to occur in rice seedlings upon submergence (Van Der Straeten et al, 2001), indicating that the hormonal change was neither restricted to the adult stage nor to one particular stem part at that stage. Even though data on endogenous GA levels in nodes of adult plants are missing, we showed that a specific set of epidermal cells and adventitious roots at the nodes are competent to respond to elevated GA levels in the presence of ethylene.…”
Section: Discussionmentioning
confidence: 64%
“…Submergence causes accumulation of ethylene, a decrease in ABA, and an increase in bioactive gibberellic acids (Hoffmann-Benning and Kende, 1992;Azuma et al, 1995;Van Der Straeten et al, 2001). The alteration in GA to ABA balance is induced by submergence in seedlings (Van Der Straeten et al, 2001) as well as in adult deepwater rice plants (HoffmannBenning and Kende, 1992). It can also be brought about by application of ethylene (Hoffmann-Benning and Kende, 1992), indicating that ethylene may be responsible for these changes in GA and ABA levels.…”
mentioning
confidence: 99%
“…It is known that in the case of deepwater rice stem elongation under submergence is due to the increase of ethylene content in the tissues (due to less diffusion under water but also to enhanced new synthesis), [2][3][4]12 that stimulates GA biosynthesis. A similar conclusion was obtained in the case of the tall lowland rice cultivar IR36.…”
Section: Submergence-induced Elongation Is Not Mediated By Ethylene Imentioning
confidence: 99%
“…A similar conclusion was obtained in the case of the tall lowland rice cultivar IR36. 4 We therefore investigated whether ethylene was also active in enhancing lowland rice seedling elongation of the Bomba and Senia cultivars. Interestingly, while Bomba seedling elongated in response to ethylene or 1-aminocyclopropane-1-carboxylic-acid (ACC; an ethylene precursor) application, as expected, Senia seedlings did not.…”
Section: Submergence-induced Elongation Is Not Mediated By Ethylene Imentioning
confidence: 99%